PENGARUH DZIKIR TERHADAP KECEMASAN DAN KOPING RELIGIUS PASIEN HEMODIALISIS: PENGARUH DZIKIR TERHADAP KECEMASAN DAN KOPING RELIGIUS PASIEN HEMODIALISIS - Kisfandari, Asri Putri; Wardani, Ratna (WELL BEING, 2024)
Chronic Kidney Failure is a progressive and irreversible kidney function disorder where the body is unable to maintain fluid and electrolyte balance, resulting in uremia. In general, cases of chronic kidney failure undergoing hemodialysis are increasing every year, especially in developing countries. The anxiety and decreased coping experienced by patients suffering from chronic kidney failure undergoing hemodialysis is due to a lack of support and enthusiasm from the family, funding for treatment and costs to meet living needs.A literature search was carried out based on articles published between 2018-2023 according to the inclusion and exclusion criteria that had been determined using 1 data base, namely Google Schoolar. This literature search uses the PRISMA guideline in carrying out the screening process. From the search results, 200 articles were obtained. After carrying out the screening process, there were 8 articles that met the criteria and will be analyzed.Based on a study of 8 pieces of literature, it was found that the hemodialysis process affects clients' religious anxiety and coping.From the results of a literature review of 8 journals, it was found that dhikr was able to reduce anxiety levels because the client felt calmer Keywords: Dhikr, anxiety, religious coping